Impact of Educational Flash Cards on Improved Learning of Skull Radiotherapy Techniques - Gholamreza Dashti; Farhad Golshan Iranpour; Marziyeh Salimi; Mojtaba Akbari; Fatemeh Mohammadi Chamnari; Nazem Ghasemi (Negah Institute for Scientific Communication, 2018)
Learning skull radiography techniques is time consuming and difficult, due to the variety of these techniques. Each year, poor employee performance of the radiology unit, impose repetitive radiographs, and a heavy burden on the health system, as well as double exposure of patients and staff. According to the results of the current investigation, comparing student's opinions revealed that the use of flash cards could facilitate and accelerate learning of radiographic techniques. Moreover, it is demonstrated that using flash cards could help maintain long-term radiographic techniques and are effective in the education process. This report highlights that the use of flash cards not only facilitates and accelerates the learning of the skull radiographic techniques, but also can reduce the repetitive radiographs, the costs imposed on the health system and double exposure of patients and staff.